Design and development of a novel additively manufactured geothermal heat exchanger. (25th October 2021) - Kabirnajafi, Mohammadmehdi; Gemeda, Takele; Demisse, Wondwosen; Estrada, Sandy; Wang, Lei; Xu, Jiajun
Summary: The existing geothermal heat exchangers pose a complex installation process and occupy large spaces which can potentially be cost‐prohibitive to many potential users. In the present study, an additively manufactured heat exchanger was designed and developed to address this issue. The designed heat exchanger can be integrated with conventional geothermal heating and cooling systems for improved efficiency and easy installation. The additively manufactured heat exchanger developed in the present study eliminates the current need to excavate the soil and install the long piping as conventionally required for the existing geothermal systems. The prototype of the proposed geothermal heat exchanger was designed using CREO software and fabricated using the direct metal laser sintering technique (DMLS) to be integrated into a heat pump to exchange heat between a constant temperature of a water bath circulator and a water heat sink. Furthermore, the support structure model generated for metal printing of the proposed geothermal heat exchanger was exposed and discussed. Two customized geothermal heating and cooling modes were separately developed to evaluate the heat transfer performance of the heat exchanger analytically and numerically. Using the analytical approach, the system sizing was designated based on the metal additive manufacturing and thermal considerations, and then average heat transfer coefficients and pressure drops were estimated for a range of mass fluxes lying in the transitional and turbulent regimes. The distributions of wall temperature, fluid's bulk temperature, and fluid's velocity along the helically‐coiled channel of the heat exchanger was also investigated numerically using the COMSOL‐Multiphysics. Lastly, a detailed cost analysis was conducted to estimate the total cost per part for the prototype fabricated using the DMLS technology. Novelty Statement: A novel ground‐source heat exchanger was additively fabricated using the direct metal laser sintering (DMLS) technique. The unique compact screw‐type design eliminates the need of excavating soil and features easy installation with less maintenance costs. Heat transfer characteristics of the proposed design were evaluated analytically and numerically. The proposed geothermal heat exchanger contributes effectively to the deployment of sustainable energy systems. Abstract : An additively manufactured geothermal heat exchanger was designed and developed via Direct‐Metal‐Laser‐Sintering technique to demonstrate an innovative approach of utilizing geothermal energy. The geothermal heat exchanger developed here eliminates the current need to excavate the soil and install the long piping as conventionally required for the common geothermal systems, while the modular design allows it for easy scaling to meet different thermal loads. A detailed cost analysis was conducted to estimate the total cost per part for this prototype.